The Effect Water Consumption On Reduction Of Leukocyte And Nitrite Levels Of Pregnant Women's Urine - Vera Iriani Abdullah; Fitra Duhita (Jurnal Kebidanan dan Kesehatan Tradisional, 2022)
Background: The incidence of asymptomatic bacteria in the population of pregnant women is around 70%, and the assessment of mortality in the world is similar. One effort that can be made is by consuming water in sufficient quantities to help rinse and dilute urine. This study aimed to analyze differences in urine levels (leukocytes and nitrite) as an indicator of asymptomatic bacteria before and after being given treatment. Methods: This study used a quasi-experimental design with a pre-post-test control group approach. A sample of 32 people was divided into two groups. The intervention group was given scheduled water consumption treatment, and the control group was given an educational intervention related to water consumption. The sample selection using a survey technique means that all pregnant women are tested for urine, and those who meet the inclusion criteria are selected as respondents. This research was conducted in the working area of the West Sorong Health Center, involving 32 respondents who were divided into 2 groups. Collecting data using observation sheets Analysis using the Chi-Square test Results: There was a significant effect on the nitrite value (p-value 0.022) in pregnant women who consumed scheduled water, but it did not significantly affect the leukocyte value (p-value 0.904). Conclusion: Pregnant women who consume water regularly (2 liters a day) will have lower levels of nitrite and leukocytes than pregnant women who do not consume water on a scheduled basis.